Konflik Sosial dalam Anime One Piece Arc Fish-Man Island - Asari, Tri Dewi; Febrianty, Fenny (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study aims to analyze the power relations between humans and Fish-Men in the One Piece Arc Fish-Man Island. The conflict presented in this arc depicts social tensions caused by discrimination and inequality, which shape the personalities and attitudes of the characters. The research employs a qualitative descriptive method with a structural analysis approach to examine the intrinsic elements of characterization, combined with Michel Foucault’s theory of power relations to interpret the dynamics of domination and resistance between the two races. The findings reveal that the characterization of Fish-Man figures such as Hody Jones and Arlong represents collective trauma and hatred toward humans as a consequence of historical oppression. In contrast, the character Jinbe embodies reconciliation through wisdom and efforts to establish equality. The power relations between humans and Fish-Men demonstrate patterns of domination that oppress, but also open space for resistance and negotiation. Thus, the Fish-Man Island Arc does not merely portray physical battles but also serves as a symbolic representation of the struggle against discrimination and the pursuit of social justice. Keywords: One Piece, Fish-Man Island, Characterization, Power Relations, Discrimination